Unethical pro-organizational behavior and actors’ work attitudes, behaviors, and performance: a meta-analysis - Li, Zhuojie; Wang, Xiaozhan; Jurek, Paweł; Wei, Leiru (Frontiers in Psychology, 2026)
IntroductionUnethical Pro-Organizational Behavior (UPB), as a special extra-role behavior with both pro-organizational and unethical characteristics, its impact on actors’ work outcomes has not yet reached a consensus. To address this gap, this study adopts a meta-analytic approach.MethodsBased on Affective Events Theory, this study conducts a meta-analysis of 44 literature (including 55 independent studies, 182 effect sizes, and 18,074 research samples) to systematically integrate the relationships and boundary conditions between UPB and actors’ work attitudes, work behaviors, and work performance, and explore the mediating role of emotions.ResultsThe results show that: (1) UPB is significantly positively correlated with negative work attitudes (r̄ = 0.242, 95% CI = [0.098, 0.376]), organizational citizenship behavior (OCB) (r̄ = 0.226, 95% CI = [0.070, 0.372]), and deviant workplace Behavior (DWB) (r̄ = 0.232, 95% CI = [0.127, 0.331]), but not significantly correlated with positive work attitudes (r̄ = − 0.078, 95% CI = [−0.388, 0.248]) and work performance (r̄ = 0.125, 95% CI = [−0.049, 0.292]). (2) Boundary condition tests show that sampling methods (multi-wave vs. cross-sectional), cultural backgrounds (Eastern vs. Western) and gender have significant moderating effects on the above relationships. Specifically, multi-wave sampling strengthens the association between UPB and negative work attitudes; under Eastern cultural backgrounds, the impact of UPB on OCB and DWB is stronger; the higher the proportion of females, the weaker the association between UPB and DWB. (3) Mediating mechanism analysis reveals that UPB indirectly reduces negative work attitudes and indirectly promotes OCB through positive emotions. However, the mediating role of positive emotions in the relationship between UPB and DWB is not significant. Additionally, it indirectly promotes negative work attitudes through negative emotions, while the mediating role of negative emotions in the relationships between UPB and both OCB and DWB are not significant.DiscussionThe conclusions of this study reveal the complexity of UPB’s impact and the key mediating role of emotions, providing theoretical basis and practical enlightenment for organizations to manage employees’ UPB.